Exploring diflunisal as a synergistic agent against Staphylococcus aureus biofilm formation - Salazar, Maria; Shahbazi Nia, Siavash; German, Nadezhda A.; Awosile, Babafela; Sabiu, Saheed; Calle, Alexandra (Frontiers in Microbiology, 2024)
Staphylococcus aureus is a bacterial pathogen of considerable significance in public health, capable of inducing a diverse range of infectious diseases. One of the most notorious mechanisms used by S. aureus to survive and colonize the site of infection is its ability to form biofilms. Diflunisal, a nonsteroidal anti-inflammatory drug (NSAID), is a known inhibitor of the Agr system in S. aureus, which is key in regulating biofilm formation. This study evaluated the effect of broad-spectrum antibiotics in combination with diflunisal on S. aureus biofilm density. Eight antibiotics were tested independently at different concentrations and in combination with diflunisal to assess their effect on S. aureus biofilm formation. When using the antibiotics alone and with diflunisal, a significant control effect on biofilm formation was observed (P<0.05), irrespective of diflunisal presence, but didn´t achieve a complete biofilm growth inhibition. Over time, diflunisal influenced biofilm formation; however, such an effect was correlated with antibiotic concentration and exposure time. With amikacin treatments, biofilm density increased with extended exposure time. In the case of imipenem, doripenem, levofloxacin, and ciprofloxacin, lower doses and absence of diflunisal showed higher control over biofilm growth with longer exposure. However, in all cases, diflunisal did not significantly affect the treatment effect on biofilm formation. In the absence of antibiotics, diflunisal significantly reduced biofilm formation by 53.12% (P<0.05). This study suggests that diflunisal could be a potential treatment to control S. aureus biofilms, but it does not enhance biofilm inhibition when combined with antibiotics.Recent studies have explored the use of broad-spectrum antibiotics commonly used on Gramnegative bacteria as alternatives for Gram-positive resistant strains. Examples of these antibiotics include amikacin, gentamicin, and tobramycin, which have been shown to be highly effective against S. aureus, including MRSA strains, due to their time and concentration-dependent properties (Hess et al.